Single and Consecutive Applications of Superhydrophobic aPDT over an in vivo Model of Periodontitis - de Souza Rastelli, Alessandra Nara [UNESP]; Tonon, Caroline Coradi; Bodahandi, Chathuna; Hasan, Tayyaba; Xu, QianFeng; Greer, Alexander; Lyons, Alan M. (Elsevier, 2025)
Significance Periodontitis is an inflammatory and multifactorial disease, and has been described as one of the most common oral diseases worldwide. Approach Wistar rats (n=148) were subjected to the periodontitis model by the use of a cotton ligature during 7 days. The superhydrophobic (SH) device was dopped with verteporfin (V) or Ce-6 (Ce) for single or consecutive (days 0, 1 and 2) applications using 60 and 125 J/cm2. Mechanical debridement associated or not with chlorhexidine were used as positive and negative controls. CFU counting, clinical parameters, histological and inflammatory conditions were evaluated. Results Three consecutive applications of SH-aPDT decreased P. gingivalis load compared to single and the control groups (p<0.05). Clinical parameters were also improved (p<0.05). Histological and stereometric analyses showed that consecutive applications were more effective than single promoting healing and reducing inflammation. Conclusions SH-aPDT could be an important tool to inhibit biofilm formation while promoting healing and anti-inflammatory responses.